2022
DOI: 10.3390/jcm11041043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cervical Transcutaneous Spinal Cord Stimulation on Sensorimotor Cortical Activity during Upper-Limb Movements in Healthy Individuals

Abstract: Transcutaneous spinal cord stimulation (tSCS) can improve upper-limb motor function after spinal cord injury. A number of studies have attempted to deduce the corticospinal mechanisms which are modulated following tSCS, with many relying on transcranial magnetic stimulation to provide measures of corticospinal excitability. Other metrics, such as cortical oscillations, may provide an alternative and complementary perspective on the physiological effect of tSCS. Hence, the present study recorded EEG from 30 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 47 publications
1
13
2
Order By: Relevance
“…This would mirror similar work by Lopez-Larraz et al which showed that ERD was significantly enhanced in a chronic C4 AIS A tetraplegic individual following four sessions of upper-alpha band neurofeedback training (25). Instead ERD was strong throughout the study and comparable to the activity of able-bodied individuals (46,53). Perhaps this disparity is attributable to the participant in the current study having some residual control over his fingers, whereas the participant in the study by Lopez-Larazz et al had no control below the elbow.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This would mirror similar work by Lopez-Larraz et al which showed that ERD was significantly enhanced in a chronic C4 AIS A tetraplegic individual following four sessions of upper-alpha band neurofeedback training (25). Instead ERD was strong throughout the study and comparable to the activity of able-bodied individuals (46,53). Perhaps this disparity is attributable to the participant in the current study having some residual control over his fingers, whereas the participant in the study by Lopez-Larazz et al had no control below the elbow.…”
Section: Discussionsupporting
confidence: 85%
“…His maximum tolerable intensity at both stimulation sites was consistent across both arms of the study, at around 47 and 40 mA for the rostral and caudal electrode. It is of interest to note that these stimulation intensities were within the range previously demonstrated with able-bodied individuals using their maximum tolerance ( 45 , 46 ).…”
Section: Resultsmentioning
confidence: 61%
“…As illustrated in Figures 1A,B circular cathode electrode with a diameter of 3 cm (ValuTrode, Axelgaard Manufacturing Co., Ltd., USA) was positioned in the C4-C6 intervertebral space. Two rectangular 8.5 × 6 cm inter-connected anode electrodes (Guangzhou Jetta Electronic Medical Device Manufacturing Co., Ltd., China) were placed bilaterally over the acromioclavicular joints ( Barss et al, 2020 ; McGeady et al, 2022a ; McGeady et al, 2022b ). The cervical spinal nerves at the C4-C6 intervertebral space were selected for stimulation due to their role in providing motor control and sensation to the UE muscles based on their branching spinal levels ( Kayalioglu, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…They studied whether stimulation applied for ten minutes in able-bodied individuals would alter corticospinal and spinal reflex activity at rest, yet found no modulation of motor evoked potentials or posterior root-muscle reflexes during or after the intervention. Likewise, McGeady and colleagues, who applied cervical stimulation for 10 min at the individually maximum tolerable intensity, found no consistent alterations in cortical oscillatory dynamics across their cohort of neurologically intact participants [8]. However, a weak inhibitory effect at cortical level was observed in those individuals who received the stimulation at the highest intensity levels.…”
mentioning
confidence: 94%